PENINGKATAN KEMAMPUAN KEPALA SEKOLAH DALAM MENYUSUN PROGRAM SUPERVISI PENDIDIKAN MELALUI MUSYAWARAH KERJA KEPALA SEKOLAH (MKKS) BERBASIS PENDAMPINGAN DI SEKOLAH BINAAN - Nuritawati Nuritawati (JURNAL MANAJEMEN PENDIDIKAN, 2019)
Emai: nuritawati16@gmail.com ABSTRACTBased on observations made by researchers to principals in target schools, namely in SDN 04 Nanggalo, SDN 05 Nanggalo and SDN 07 Sungai Tawar, it was found that the ability of school principals to develop education supervision programs was still low. The purpose of this study was to describe and obtain information about the efforts of the school principal's ability to develop an education supervision program through the School Principal Working Meeting based on mentoring in the target school. This research is a school action research. The research procedures in this study include planning, action, observation and reflection. This study consisted of two cycles with four meetings. The subjects of the study consisted of 3 principals of the target schools. The research data was collected using observation sheets. Data were analyzed using percentages. The results of the study showed that Mentoring-based MKKS could improve the ability of school principals in developing education supervision programs in target schools. This is evidenced by the increase in the ability of school principals to develop educational supervision programs from cycle I to cycle II. The average ability of the principal in preparing the education supervision program in the first cycle was 73.17 with sufficient categories and in the second cycle 84.29 in the good category